2018
DOI: 10.1093/jnci/djy018
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells in Breast Cancer Patients Treated by Neoadjuvant Chemotherapy: A Meta-analysis

Abstract: CTC count is an independent and quantitative prognostic factor in early breast cancer patients treated by NCT. It complements current prognostic models based on tumor characteristics and response to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
186
6
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 227 publications
(206 citation statements)
references
References 20 publications
10
186
6
4
Order By: Relevance
“…In addition, an in vivo animal experiment also indicated that NCT could promote luminal BC cell intrusion into the circulation . On the other hand, a meta‐analysis included 1574 BC patients who underwent NCT and evaluated the CTC numbers with CellSearch at baseline and before surgery; although there was no significant correlation between the pCR and CTC detection before surgery, the CTC count was lower than the baseline count ( P < .001) . Here, our results also revealed that CTC numbers decreased with NCT, and we did not find a definite correlation between CTC changes and the pCR rate, but the patients with positive CTCs at baseline and converted to negative CTCs after NCT had a higher pCR ratio compared to that in patients in the other groups, which suggested a potential pCR predictive value of CTC numeration in patients with CTCs detected before NCT.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In addition, an in vivo animal experiment also indicated that NCT could promote luminal BC cell intrusion into the circulation . On the other hand, a meta‐analysis included 1574 BC patients who underwent NCT and evaluated the CTC numbers with CellSearch at baseline and before surgery; although there was no significant correlation between the pCR and CTC detection before surgery, the CTC count was lower than the baseline count ( P < .001) . Here, our results also revealed that CTC numbers decreased with NCT, and we did not find a definite correlation between CTC changes and the pCR rate, but the patients with positive CTCs at baseline and converted to negative CTCs after NCT had a higher pCR ratio compared to that in patients in the other groups, which suggested a potential pCR predictive value of CTC numeration in patients with CTCs detected before NCT.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, recent reports indicate that patients who receive NCT and have residual disease could benefit from following intensive or prolonged treatment . Multiple approaches have been applied to investigate the effectiveness of NCT, such as Ki67, MRI, and PET scanning, while the potential value of CTC in NCT of BC has only been reported in a few studies …”
Section: Introductionmentioning
confidence: 99%
“…The clinical utility of CTC enumeration as a prognostic marker in nonmetastatic breast cancer patients treated by neoadjuvant chemotherapy was recently shown in a meta‐analysis using the CellSearch system. This meta‐analysis, based on 21 studies, has shown that CTC count is an independent and quantitative prognostic factor in early breast cancer patients treated by neoadjuvant chemotherapy, and complements current prognostic models based on tumor characteristics and response to therapy . A very recent clinical prospective study that included 156 women with newly diagnosed metastatic breast cancer concluded that longitudinal evaluation of CTC and CTC clusters improves prognostication and monitoring in patients with metastatic breast cancer starting first‐line systemic therapy …”
Section: Circulating Tumor Cellsmentioning
confidence: 79%
“…This meta-analysis, based on 21 studies, has shown that CTC count is an independent and quantitative prognostic factor in early breast cancer patients treated by neoadjuvant chemotherapy, and complements current prognostic models based on tumor characteristics and response to therapy. 39 A very recent clinical prospective study that included 156 women with newly diagnosed metastatic breast cancer concluded that longitudinal evaluation of CTC and CTC clusters improves prognostication and monitoring in patients with metastatic breast cancer starting first-line systemic therapy. 40 Detection of CTCs using the CellSearch system before neoadjuvant therapy was an independent prognostic factor of impaired clinical outcome, and when combined with pathologic complete response (pCR), it was shown to be helpful to stratify breast cancer patients for therapeutic interventions.…”
Section: Breast Cancermentioning
confidence: 99%
“…For example, some experimental approaches utilize the detection of circulating microRNAs owing to their relatively good stability in body fluids. In addition, a number of investigational diagnostic procedures rely on the isolation and analysis of circulating tumor cells (Antonarakis et al, 2014; Dasgupta et al, 2017; Siravegna et al, 2017; Bidard et al, 2018). …”
Section: Liquid Biopsymentioning
confidence: 99%